2019
DOI: 10.21608/ejrs.2019.45672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Some Doe, Litterand Lactiontraits of New Zealand White Rabbits

Amira El-Deghadi

Abstract: Data collected on 765litters produced from 261 does and 69 sires of New Zealand White for five consecutive years. The data of doe traits (DBW = doe body weight, DPE = doe production efficiency), litter traits (LSB = litter size at birth, LSW = litter size at weaning, LW1, LW2, LW3 and LW4 = litter weight at 1 st , 2 nd , 3 rd week and 4 th week of age respectively, litter gain traits (LG1= litter gain from birth to 1 st week, LG2= litter gain from birth to 2 nd week, LG3= litter gain from birth to 3 rd week, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
6
4
0
Order By: Relevance
“…The LWW is determined by the number of kits born and the mother’s milk capacity since she maintains the homogeneous weight in the litter, reduces competition in the udder, and increases its viability [ 9 ]. The LWW in this study was similar to that of Agea et al [ 18 ] and lower than the finding of El-Deghadi [ 3 ]. Then, the weight of the kits at weaning (WW) depends on the size of the litter, the weight being lower when the litter size is high [ 20 ]; from Table 1 , it is inferred that the average size of the litter at weaning was 5.68 kits, with a WW of 423.7 ± 14.5 gm.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The LWW is determined by the number of kits born and the mother’s milk capacity since she maintains the homogeneous weight in the litter, reduces competition in the udder, and increases its viability [ 9 ]. The LWW in this study was similar to that of Agea et al [ 18 ] and lower than the finding of El-Deghadi [ 3 ]. Then, the weight of the kits at weaning (WW) depends on the size of the litter, the weight being lower when the litter size is high [ 20 ]; from Table 1 , it is inferred that the average size of the litter at weaning was 5.68 kits, with a WW of 423.7 ± 14.5 gm.…”
Section: Resultssupporting
confidence: 88%
“…Similar results for various litter-related traits were presented by Pycha et al [ 15 ], Behiry et al [ 30 ], and Karim et al [ 41 ]. For the WW and CW traits, the values obtained from r tend to be moderate; similar reports were presented previously [ 3 , 9 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In general, estimates of h 2 a for litter traits were lower and ranged from 0.05 to 0.08 for litter size traits, 0.09 for both litter weight traits, and 0.14 for pre-weaning litter gain. These estimates were consistent with estimates of h 2 a in the relevant literature (Abou-Khadiga et al, 2012;El-Deghadi, 2019;Habib, 2011;Nagy et al, 2014;Nguyen et al, 2017). Consistent with these studies, the lower estimates of h 2 a for litter traits may be due to the relative importance of additive genetic factors being low.…”
Section: Heritability (H 2 A) and Ratio Of Permanent Environmental Va...supporting
confidence: 88%
“…CV % estimates for litter traits (Table 1) increased from birth to weaning, showing that phenotypic variance was lower at birth than at weaning. However, these estimates showed that improving these traits through phenotypic selection is quite possible (Shehab El-Din, 2016;El-Deghadi, 2019). In this respect, Youssef et al (2008) suggest that the higher variation in litter traits at weaning than at birth would lead to greater phenotypic improvement in these traits by selection associated with good management during the suckling period.…”
Section: Meansmentioning
confidence: 99%